2009
DOI: 10.4321/s0365-66912009000700004
|View full text |Cite
|
Sign up to set email alerts
|

Guías de práctica clínica de la SERV: Tratamiento de la degeneración macular asociada a la edad (DMAE) exudativa

Abstract: RESUMENObjetivo: La Degeneración Macular Asociada a la Edad (DMAE) en su forma húmeda supone una grave enfermedad que condiciona ceguera legal en muchos pacientes y con mal pronóstico si no es tratada. Pretendemos establecer una guía de actuación clínica con las diferentes opciones terapeúticas que existen en el momento actual, que puedan ayudar al oftalmólogo en su práctica clínica. Métodos: Un grupo de expertos en retina médica seleccionados por la SERV han evaluado los resultados de los diferentes estudios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
(40 reference statements)
0
22
0
1
Order By: Relevance
“…Likewise, the Lumiere study reflected poor compliance with treatment recommendations in France [11]. For example, the SERV Guideline and three German ophthalmologic societies recommend a loading treatment initiation followed by monthly follow-up visits to detect early recurrences and perform prompt retreatments to avoid as much as possible the permanent anatomic and functional damage [9, 10]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the Lumiere study reflected poor compliance with treatment recommendations in France [11]. For example, the SERV Guideline and three German ophthalmologic societies recommend a loading treatment initiation followed by monthly follow-up visits to detect early recurrences and perform prompt retreatments to avoid as much as possible the permanent anatomic and functional damage [9, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…The Phase III MARINA and ANCHOR trials with ranibizumab were designed with fixed monthly injections over a period of two years [7, 8]. However, as this treatment strategy is difficult to undertake in the regular clinical practice, other alternative approaches have been proposed by some retina specialist societies from several European countries, like the Spanish Society of Retina and Vitreous (SERV), recommending an initial loading dose followed by maintenance injections on an as-needed basis (PRN: per re nata ) according to visual acuity and optical coherence tomography (OCT) changes [9]. Likewise, three German ophthalmologic societies [10] (der Retinologischen Gesellschaft, der Deutschen Ophthalmologischen Gesellschaft und des Berufsverbands der Augenärzte Deutschlands e.V.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients included had treatment-naive exudative AMD and started treatment between January 1, 2008, and December 31, 2010, with intravitreal ranibizumab following the Spanish Society of Retina and Vitreous protocol treatment [ 4 ]. Spanish and European guidelines recommended at that time a loading dose consisting of three initial consecutive monthly injections and thereafter an as needed treatment, also known as pro re nata (PRN), where injections are administered when visual acuity loss and signs of lesion activity occur [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In pivotal clinical trials, ranibizumab was administered every month for 2 years and good functional results were obtained. However, subsequent studies theorized that a judiciously administered course of variable-frequency pro re nata intravitreal ranibizumab treatment preserves vision in three quarters of patients and improves vision in one third becoming the accepted protocol [ 3 , 4 ]. Several authors have reported clinical practice outcomes and adherence to this treatment regime in different European countries [ 5 7 ], but only one study presented results beyond 1 year of follow-up [ 8 ].…”
Section: Introductionmentioning
confidence: 99%